Plant mating system dynamics in restoration: a comparison of restoration and remnant populations of Hakea laurina (Proteaceae). Issue 7 (18th July 2022) - Fernandes, Rianne E.; Millar, Melissa A.; Coates, David J.; Byrne, Margaret; Krauss, Siegfried L.; Williams, Matthew R.; Hopper, Stephen D.
Abstract : Ecological restoration is addressing the challenge of biodiversity conservation in landscapes where native vegetation has been extensively cleared. Reestablishing ecological interactions that support self‐sustainable populations plays an essential role in restoration efforts. For animal‐pollinated plant species, comparing mating system dynamics within restoration populations with natural remnant populations can inform the progress of restoration activities. We assessed mating system parameters, seed weight, invertebrate floral visitors, and genetic diversity for two restoration populations and two native reference remnant populations of the animal‐pollinated, woody shrub/tree, Hakea laurina (Proteaceae) in the Southwest Australian Floristic Region. There was no difference in outcrossing rates between the two sites (restoration and reference populations combined) or treatments (sites combined). However, one restoration population showed significantly lower outcrossing that was correlated with reduced seed weight, greater inbreeding, and significantly lower invertebrate richness and abundance compared to its nearby remnant population. In contrast, in the other restoration population, all measures were comparable to the reference remnant population. Local genetic diversity available in remnant populations was captured in both restoration populations. Limitations to pollinator services may be affecting mating patterns and potentially population fitness, in a younger restoration population with reduced proximity to remnant vegetation, which has a tall coplanted overstorey species and spatially aggregated individuals. We highlight these aspects of restoration populations as important areas of ongoing research that will impact the reestablishment of ecological interactions, and the assessment of mating system dynamics as a valuable tool to inform the current progress of restoration activities.